Mobile Communication Technology in Agriculture and Rural Development; A Qualitative study on Tamil Mobile Apps on Agriculture - Abinesh, AK; Jebakumar, C (Journal of Advanced Research in Journalism & Mass Communication, 2018)
The progressive use of mobile communication has created great prospect towards social, economic empowerment and also development in grassroots innovation in developing countries. Mobile communication has brought in great revolution in the field of agriculture by providing vide scope of agricultural development through access of information on modern agricultural practices, agricultural market, new crops, weather, pests control and so on. Mobile technology has brought in confidence among farmers to communicate directly in getting advice related to agriculture and also to sell the product directly to the market without hindrance from third party brokers. Also due to the various initiatives by government of India many projects on technology based communication become easily accessible by farmers of all sectors. This study mainly focus in assess and understand the functionality of the regional Tamil mobile apps on agriculture in Tamilnadu based on the Mobile Apps rating scale (MARS- Mars is designed to analyse mobile apps based on the criteria of engagement, functionality, aesthetics and information quality) and how effective it can be in bringing development in Agriculture. This study will provide more opportunities for policy makers to effectively harness mobile application and to bring sustainable development in agriculture. How to cite this article: Abinesh AK, Jebakumar C. Mobile Communication Technology in Agriculture and Rural Development; A Qualitative study on Tamil Mobile Apps on Agriculture. J Adv Res Jour Mass Comm 2018; 5(4): 167-173. DOI: https://doi.org/10.24321/2395.3810.201835